Effect of a proposal of exercises on the development of basic motor abilities in men’s artistic gymnastics - Adham Ali, Othman; Hamid Ahmed, Wissam; Saeed Abd, Abdul Qader; Nafi Hummadi, Jasim (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The purpose of this study was to recognize the effect of the proposed exercises in developing the particular motor abilities employed in the study as well as some ground skills in men’s artistic gymnastics. This study used the experimental method and included 14 players of the directorate of Anbar Education team in the technical gymnastics for men (junior category), aged 10-12 years. The proposed exercises were then performed, which included 30 training units over a ten-week period, three training units each week, and forty minutes of training per unit. The researchers used the Statistical Package for the Social Sciences (SPSS) for data analysis. The results of our study showed that there were statistically significant differences in the results of the pre- and post-tests in all variables of the elements of special motor abilities and ground skills of the research sample, in favor of the post-test (p < 0.05). The use of the proposed exercises had a positive effect in developing some special motor skills, and the development of special motor abilities contributed to the development of ground skills in the artistic gymnastics for men.